Making technology investments profitable : ROI road map from business case to value realization - Keen, Jack M. (Hoboken, N.J. : Wiley, 2011)
Filled with case studies, this innovative book enables managers to confidently quantify, in a matter of minutes, the true business value of funding a desired project. New edition explains how to proactively manage the conversion of a business case's value promise to its value realization Includes dozens of new case studies on realizing maximum value from IT enabled investments from various industries and around the world.
Includes bibliographical references (p. 275-277) and index.
oif 11/06/15
Loan
Keywords: Information technology -- Management; Information technology -- Economic aspects